Pembangunan Aplikasi Pemesanan Gas Elpiji Online Berbasis Android - Muhammad Irfan Nurhakim; Henry Septanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to make the order application design of gas LPG that can give periodically information about availability of gas stock on interface application and it can rapidly manage order data, because there is notification that announce to user application when gas was ordered. The development system of this application uses development method Rational Unified Process (RUP) with uses system modeling Unified Modelling Language (UML) and implementing the Firebase Cloud Messaging service for sending notifications when there is information on gas ordering activity, notifications received by the user whether the application is closed or open. In addition, application users can view the history of successful or failed order transactions. The final result that obtained from this research is an online LPG gas ordering application based on android.